2023
DOI: 10.1111/brv.12988
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the deep: mechanisms behind diversification of eukaryotic protein complexes

Abstract: Genetic variation is the major mechanism behind adaptation and evolutionary change. As most proteins operate through interactions with other proteins, changes in protein complex composition and subunit sequence provide potentially new functions. Comparative genomics can reveal expansions, losses and sequence divergence within protein‐coding genes, but in silico analysis cannot detect subunit substitutions or replacements of entire protein complexes. Insights into these fundamental evolutionary processes requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 243 publications
0
8
0
Order By: Relevance
“…2). Instead, we propose that the sparse distribution likely arises from ongoing and repeated gene loss, as has been previously documented for other gene families across the Tree of Life [22,[24][25][26].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…2). Instead, we propose that the sparse distribution likely arises from ongoing and repeated gene loss, as has been previously documented for other gene families across the Tree of Life [22,[24][25][26].…”
Section: Discussionmentioning
confidence: 61%
“…1B). We believe this pattern reflects a pattern of ongoing, repeated gene losses across eukaryotes, as has been found for other innate immune proteins [21][22][23] and other types of gene families surveyed across eukaryotes [22,[24][25][26]. We found that BUSCO completeness scores and data type (genomes vs. transcriptomes) were insufficient to explain the pattern of gene loss (Supp.…”
Section: Discovering Immune Homologs Across the Eukaryotic Tree Of Lifementioning
confidence: 60%
“…Interestingly, in this case occasional gene loss might open up space for a duplicated gene to step in. [ 83 ] Duplications also allow more optimal “gene sharing,” for example, letting a metabolic enzyme become an eye lens crystallin. [ 84 ] Reconstructed gene trees might thus come up with ancient ancestral forms of diverged proteins, helping us understand how certain structures and functions evolved, even in the case of proteins now having completely different functions.…”
Section: Broader Applicability Of the Concept Of Trees Growing By Des...mentioning
confidence: 99%
“…found for other innate immune proteins [27][28][29] and other types of gene families surveyed across eukaryotes [28,[30][31][32]. Indeed, many of the species that lacked any of the immune homologs were represented by high-quality datasets (Ex: Metazoa, Chlorplastida, and Fungi).…”
Section: Plos Biologymentioning
confidence: 99%